FACTORS ASSOCIATED WITH VERY PRETERM AND EXTREMELY PRETERM INFANTS AT THAI NGUYEN CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To analyze factors associated with very preterm and extremely preterm birth among preterm infants at Thai Nguyen Central Hospital.Methods: A cross-sectional descriptive study was conducted on 110 preterm infants (
Keywords: Neonates, preterm birth, associated factors, extremely preterm, very preterm